From Cold War to Cyber War : The Evolution of the International Law of Peace and Armed Conflict over the last 25 Years - Heintze, Hans-Joachim; Thielbörger, Pierre (Springer International Publishing : Imprint: Springer, 2016)
This book follows the history of the international law of peace and armed conflict over the last 25 years. It highlights both the parameters that have remained the same over the years as well as the new challenges now facing international law. The articles analyze new developments concerning the prohibition of the use of force in international relations, self-determination of peoples, human rights and human security as well as international coordination of humanitarian assistance.